Investigating Metaphors of COVID-19 – in Related English Texts (College of Basic Education Research Journal, 2025)
This study investigates metaphors in COVID-19- related English texts. The study shows an overview on how people are suffer from  pandemic and its negative effects, it is not preferable to talk about COVID-19 always explicitly. Metaphorical expressions assist in conveying  meaning successfully. They are essential in transferring  message of  text appropriately and successfully for they are capable of adding force to the meaning conveyed. Study  utilized Conceptual Metaphor Theory by Lakoff and Jonson (1980) as a model to analyze chosen data. Conceptual Metaphor Theory has been adapted by adding frames and  mind maps to simplify  metaphorical project from  source domain onto  target domain. Data are selected from English social media like Twitter, Facebook, and other websites like medical websites , online articles and journals concerning  pandemic expressions related to metaphors. Ten English COVID-19 metaphorical expressions have been chosen for analysis. It is found that  virus has been used as an Abstract Target Domain. Also, it is found that Concrete Source Domains (Fire) and (war) are the most frequent ones and they  occurred five times separately out of  total number of  data.
Keywords: Metaphor; Covid – 19; Conceptual; Metaphor theory